The mysterious howling eaudiobook The mysterious howling. - Wood, Maryrose (The Incorrigible Children of Ashton Place, 2010)
Of especially naughty children, it is sometimes said: “They must have been raised by wolves.” The Incorrigible children actually were. Discovered in the forests of Ashton Place, the Incorrigibles are no ordinary children: Alexander keeps his siblings in line with gentle nips; Cassiopeia has a bark that is (usually) worse than her bite; and Beowulf is alarmingly adept at chasing squirrels.             Luckily, Miss Penelope Lumley is no ordinary governess. Only fifteen years old and a graduate of the Swanburne Academy for Poor Bright Females, Penelope embraces the challenge of her new position. Though she is eager to instruct the children in Latin verbs and the proper use of globes, first she must eliminate their canine tendencies.             But mysteries abound at Ashton Place: Who are these three wild creatures? Why does Old Timothy, the coachman, lurk around every corner? Will Penelope be able to civilize the Incorrigibles in time for Lady Constance’s holi-day ball? And what on earth is a schottische?             Penelope is no stranger to mystery, as her own origins are also cloaked in secrecy. But as Agatha Swanburne herself once said, “Things may happen for a reason, but that doesn’t mean we know what the reason is—at least, not yet.”